The Photographer: Deo Kyakulagira - Stultiens, Andrea (Netherlands: Paradox / HIPUganda, 2014)
Do you know the movie The Pianist? My dad was a Photographer. He was just like the man in the movie. His camera, His passion, saved him several times......
Do you know the movie The Pianist? My dad was a Photographer. He was just like the man in the movie. His camera, His passion, saved him several times......